Performing with computer applications - Blanc, Iris (Thomson/Course Technology, 2004)
Using the developmental approach to learning, Performing with Computer Applications, 3rd Edition offers a means of learning about computers, thinking critically, solving problems, communicating effectively, applying technology to task and working in teams. The book introduces word processing, Internet, desktop publishing, spreadsheet, database, and presentation concepts through sequential practice material. It is non-software specific so its exercises can be used with any software or operating system.